2012
DOI: 10.1007/s11748-012-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of resected synchronous multiple primary lung cancer comprising adenocarcinoma and carcinoid (cancer-in-cancer)

Abstract: We performed surgical resection of synchronous multiple primary lung cancer, comprising adenocarcinoma and carcinoid components. The latter tumor was located within the central scar tissue formed by the adenocarcinoma (cancer-in-cancer). The patient was a 67-year-old Japanese woman who had a nodular lesion in the right S1 on chest computed tomography. Lung cancer was diagnosed intraoperatively by rapid needle aspiration cytology, and right upper lobectomy with mediastinal lymph node dissection was performed. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Pathology con rmed that the tumor in the lower lobe of the right lung was bronchial carcinoid, but the tumor in the middle lobe of the right lung was adenocarcinoma. Nagamatsu et al [13] reported in 2012 a case of adenocarcinoma found in the resection of the superior lobe of the right lung, and carcinoid was detected in the central brous scar of the adenocarcinoma. Abbi et al [14] reported a case of a tumor found during resection of the superior lobe of the right lung in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology con rmed that the tumor in the lower lobe of the right lung was bronchial carcinoid, but the tumor in the middle lobe of the right lung was adenocarcinoma. Nagamatsu et al [13] reported in 2012 a case of adenocarcinoma found in the resection of the superior lobe of the right lung, and carcinoid was detected in the central brous scar of the adenocarcinoma. Abbi et al [14] reported a case of a tumor found during resection of the superior lobe of the right lung in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Nagamatsu et al reported a case of cancer-in-cancer and the resected specimen showed a carcinoid component localized within the central fibrous scar of the dominant adenocarcinoma component [ 12 ]. A case of five synchronous and metachronous lung cancers in a single patient that developed in a span of 7 years was reported in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility when considering the location of the second primary tumor is there can be a mixture of two tumors or one tumor that contains two components. Both Nagamatsu et al [5] and Sano et al [6] described this occurrence and named it "cancer in cancer" and "a mixture of two tumors", respectively. The clinical features of synchronous tumors remain unknown because they are very rare, [6] and we believe that meticulous pathological examinations are needed to reveal the presence of this mixture.…”
Section: Discussionmentioning
confidence: 99%